The relationship among psychosocial adaptation, medication adherence and quality of life in breast cancer women with adjuvant endocrine therapy - Haoran Jiang; Yu Dong; Wei Zong; Xiu-jie Zhang; Hui Xu; Feng Jin (BMC, 2022)
Abstract Background Patients undergoing endocrine therapy for breast cancer often suffer from poor psychosocial adaptation, low compliance with endocrine therapy and poor quality of life. However, the relationship among the three is not completely clear. The aims of this study were to investigate the status of psychosocial adaptation (PSA), medication adherence and quality of life (QOL) in breast cancer women with adjuvant endocrine therapy (AET), and to analyze the influencing factors of QOL and explore the relationship among them. Methods 346 breast cancer women were selected who underwent endocrine therapy after surgery, and data collected by the general information questionnaire, the PSA questionnaire among breast cancer women with AET, Morisky Medication Adherence Scale and The Functional Assessment of Cancer Therapy-Breast (FACT-B). The relationship among the variables was investigated by univariate analysis, multiple stepwise regression analysis and mediating effect analysis. Results The scores of PSA, medication adherence and QOL were slightly above the medium level. Univariate analysis showed that there were significant differences in QOL among breast cancer women of AET with different types of exercise, medical payment methods, discomfort symptoms (headache, hypomnesis, arthralgia, perturbation), type of discomfort symptoms, medication adherence and PSA; Multi-factor analysis showed that PSA and medication adherence were the influential factors of QOL; mediating effect showed that medication adherence played a partial mediating role in PSA and QOL. Conclusion The QOL of breast cancer women with AET will be directly affected by PSA. Medication compliance has a weak mediating effect in the indirect impact of PSA on the QOL. In the future, clinical nursing work should take targeted measures to improve the PSA level of patients, and effectively improve the compliance of patients with medication, so as to better improve the QOL of breast cancer women.